Alfabetização de jovens e adultos: um estudo sobre o perfil dos (as) alfabetizados (as) do município de Erechim/RS - Jevinski, Camila Paula (2018)
This present academic work presents the results of the stricto sensu postgraduate course that aims to obtain the degree of Professional Master in Education by the Universidade Federal da Fonteira Sul considering the theme: “Literacy of young and adult people: a study about the profile of individuals who are getting alphabetized in Erechim, state of Rio Grande do Sul, Brazil”. In this way, different authors from the area of Popular Education were used to support this research, basically constituted by Freire (1989, 1980, 1982, 1990) in dialogue with other interlocutors: Gadotti and Romão (2011), Paiva (2015), Paludo (2001), Schuwarts (2013), Streck (2018), among others. The case study was accomplished at the Municipal Center for Youth and Adult Education located in the city of Erechim. The first intention is to investigate the role of this institution in the fight against illiteracy in the municipal sphere, in view of the profile of young and adult people, as well as to diagnose the phenomenon of illiteracy in Erechim, including the social context of young and adult people literacy classes. Thus, let us try to verify how the pedagogical action happens with the literacy individuals, observing the current Paulo Freire’s method in the proposals of literacy of young and adult people. Therefore, we intend to understand the relation between popular class and illiteracy, as well as to investigate and diagnose the profile of these people who take part of the Youth and Adult Education Center of Erechim class, so that, this research serves as a subsidy for teachers in their pedagogical practice. The motivations of this search start from our academic and professional path, because we always focused on Education, from the perspective of Popular Education and its relevance in society. In this academic work, let us locate both of the aforementioned types of education in a historical perspective, as well as approach the literacy and the target people of this study. Finally, the writings of this research let us present the profile and the formative possibilities of the alphabetizing from Erechim. Let us reinforce that in these last writings there is no ready method, something finished, but there is a challenge: to always be in permanent formation, learning with our classmates (educators), that is, continuously research and reflect on our educational practice, so that we can revise, recreate and reinvent it constantly.